Implementation of Law Number 24 Year 2011 on Social Security Organizing Agency (BPJS) for Health (Ternate City Case Study) - M. Rusdy Namsa (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The purpose of this research is to explain the implementation of BPJS health policies and find out the root causes of health insurance BPJS in the process of implementing its policies by using the basic framework of thought from Edward III then become a reference in research so that later it can have a positive impact and benefit on society and policy makers. The qualitative research method was chosen which emphasizes more on the quality size of the entity being researched which is descriptive and tends to use analysis of the data collection process obtained by using data collection techniques in the form of interview and observation by finding accurate source validation. The results of this study indicate that in ternate City BPJS Health Participants, especially where doctors practice, still have obstacles both in terms of the health area zone and health facilities in Ternate City, while internally BPJS Health is still difficult to advocated for the government in improving human resourches and health facilities in Ternate City. All of this problem when viewed from the perspective of the implementation model developed by Edward, several factors will be found; ineffective communication, the need to evaluate the disposition, the need to increase resourches and the flexibility of the bereaucratic structure.